On-Demand Continuous Manufacturing of Ciprofloxacin in Portable Plug-and-Play Factories: Implementation and In Situ Control of Downstream Production - Capellades, Gerard; Neurohr, Clemence; Briggs, Naomi; Rapp, Kersten; Hammersmith, Gregory; Brancazio, David; Derksen, Bridget; Myerson, Allan S (Organic process research & development, 2021)
Traditional pharmaceutical manufacturing operates around a supply chain that is subject to complex logistics and is vulnerable to spikes in demand and interruptions. In this context, continuous pharmaceutical manufacturing in portable, refrigerator-sized factories is a promising solution with applications in battlefield medicine, pandemic response, and mitigation of local medical emergencies. A new iteration of the pharmacy on demand initiative is hereby presented, involving the development of equipment and processes for the manufacture of ciprofloxacin HCl with commercialization in mind. This article covers the implementation and the feedback control strategies for downstream manufacturing, as well as the results of the first end-to-end continuous manufacturing campaign. The results involve a significant leap from prior iterations, consistently attaining drug substance specifications in a fully automated process and with a 4-fold increase in the process throughput over the most recent iteration.